Homotopy Perturbation Method for Solving Generalized Riccati Differential Equation - Mechee, Mohammed S; Al-Juaifri, Ghassan A (Al-Nahrain Journal of Science, 2019)
In this work, we have studied a class of nonlinear Riccati differential equation which is used as mathematical models in many physically significant fields and applied science. The homotopy perturbation method, has been modified for solving generalized linear and nonlinear Riccati differential equation, which is a second-order ordinary differential equation. Also, we have tested the modified homotopy perturbation method on the solving of different implementations which are show the efficiency and accuracy of the proposed method. The approximated solutions are agreed well with analytical solutions for the tested problems.